Honeycomb‐like carbon materials derived from coffee extract via a "salty" thermal treatment for high‐performance Li‐I2 batteries. Issue 2 (19th March 2020) - Su, Zhong; Ling, Han Yeu; Li, Meng; Qian, Shangshu; Chen, Hao; Lai, Chao; Zhang, Shanqing
Abstract: Sustainable, conductive, and porous carbon materials are ideal for energy storage materials. In this study, honeycomb‐like carbon materials (HCM) are synthesized via a "salty" thermal treatment of abundant and sustainable coffee extract. Systematic materials characterization indicates that the as‐prepared HCM consists of heteroatoms (N and O, etc.) doped ultra‐thin carbon framework, possesses remarkable specific surface area, and excellent electrical conductivity. Such properties bestow HCM outstanding materials to be the blocking layer for Li‐I2 battery, significantly eliminating the dissolution of I2 in the cathode region and stopping the I2 from shutting to anode compartment. Furthermore, our electrochemical investigation suggests that HCM could incur surface pseudo‐capacitive iodine‐ions charge storage and contribute additional energy storage capacity. As a result, the resultant Li‐I2 battery achieves a robust and highly reversible capacity of 224.5 mAh·g −1 at the rate of 10 C. Even under a high rate of 50 C, the remarkable capacity of the as‐prepared Li‐I2 battery can still be maintained at 120.2 mAh·g −1 after 4000 cycles. Abstract : The honeycomb‐like carbon material is derived from coffee extract via a "salty" thermal treatment. Such a material is used to fabricate the blocking layer that delivers high performance in Li‐I2 batteries.